Two Xenopus Proteins That Bind the 3′ End of Histone mRNA: Implications for Translational Control of Histone Synthesis during Oogenesis - Wang, Zeng-Feng (American Society for Microbiology, 1999)
Translationally inactive histone mRNA is stored in frog oocytes, and translation is activated at oocyte maturation. The replication-dependent histone mRNAs are not polyadenylated and end in a conserved stem-loop structure. There are two proteins (SLBPs) which bind the 3′ end of histone mRNA in frog oocytes. SLBP1 participates in pre-mRNA processing in the nucleus. SLBP2 is oocyte specific, is present in the cytoplasm, and does not support pre-mRNA processing in vivo or in vitro. The stored histone mRNA is bound to SLBP2. As oocytes mature, SLBP2 is degraded and a larger fraction of the histone mRNA is bound to SLBP1. The mechanism of activation of translation of histone mRNAs may involve exchange of SLBPs associated with the 3′ end of histone mRNA.